Discovery of main group single Sb–N4 active sites for CO2 electroreduction to formate with high efficiency. Issue 9 (28th July 2020) - Jiang, Zhuoli; Wang, Tao; Pei, Jiajing; Shang, Huishan; Zhou, Danni; Li, Haijing; Dong, Juncai; Wang, Yu; Cao, Rui; Zhuang, Zhongbin; Chen, Wenxing; Wang, Dingsheng; et al.
Abstract : We discover that an Sb single atom material consisting of Sb–N4 moieties anchored on N-doped carbon nanosheets can serve as a CO2 RR catalyst to produce formate with high efficiency. Abstract : Main group antimony (Sb) species are promising electrocatalysts that promote the CO2 reduction reaction (CO2 RR) to formate, which is an important hydrogen storage material and a key chemical intermediate in many industrial reactions. Herein, we discovered that an Sb single atom (SA) material consisting of Sb–N4 moieties anchored on N-doped carbon (NC) nanosheets (named Sb SA/NC) could serve as a CO2 RR catalyst to produce formate with high efficiency. Sb SA/NC exhibited a formate faradaic efficiency of 94.0% at −0.8 V vs. RHE. In situ X-ray absorption fine structure (XAFS) investigations and density functional theory (DFT) calculations demonstrated that the excellent CO2 RR activity originated from the positively charged Sb δ + –N4 (0 < δ < 3) active sites. Our results present significant guidelines for the rational design and accurate modulation of main group metal (Sb, In, Sn, Bi, etc. ) catalysts for the CO2 RR at the atomic scale.